KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA GURU PADA SMAN 1 CALANG KABUPATEN ACEH JAYA - Juanda .; Nasir Usman; Sakdiah . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
Principal as a determinant factor of educational success in schools that have characteristics or skills that are conceptual skills skills, technical skills and humanitarian skills. This study aims to examine the policies taken by the principal in the field of administration, supervision and leadership of education to improve teacher work motivation. This research uses qualitative approach. The data were collected by using observation technique. The results showed: (1) the policy taken by the principal in the field of administration, done by providing direction and guidance for teachers relating to the management of learning that can increase motivation for teachers in carrying out their duties. (2) In the field of supervision to improve work motivation, conducted by providing guidance and direction related to the goals achieved by the teacher, guide the teacher understand the problems and needs of teachers, selecting tasks appropriate to the ability and academic background possessed by teachers and assessment of teacher. (3) Meanwhile, in terms of leadership of the principal as the leader of education in improving the motivation and performance of teachers in SMAN 1 Calang, Aceh Jaya District is done by fostering a harmonious relationship with the teacher and also with the community. So, both teachers and the community can work together to create a better education